PERAN NEGARA DALAM MENDUKUNG UMKM MELALUI AKSES PERMODALAN DAN DIGITALISASI (STUDI KASUS PADA PROGRAM KUR) - Femas Yuanda; Kristober Sitompul; Samsir, Zulpiani; Siti Syuhada; Siti Rauda; Zubaidah (Jurnal Pendidikan Ekonomi, 2025)
Abstract: Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, contributing significantly to GDP and employment. However, they face challenges in accessing formal financing, particularly through the People’s Business Credit (KUR), due to limited legality, poor financial records, and low financial and digital literacy. This study analyzes the government’s role in supporting MSMEs through financing access and digital transformation, using a qualitative descriptive approach involving interviews, observations, and documentation with MSMEs and Bank BRI in Mendalo Darat, Muaro Jambi. Findings show most MSMEs struggle to access KUR due to administrative barriers and limited guidance. Digitalization offers a strategic alternative, though hindered by limited access and skills. Government initiatives such as digital training, OSS, and financing support are essential in boosting MSME competitiveness. The study concludes that synergy between financing and digitalization policies is crucial for inclusive, sustainable MSME growth.